2021
DOI: 10.1007/s10198-021-01275-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cost-utility of phosphate binders as a treatment option for hyperphosphatemia in chronic kidney disease patients: a systematic review and meta-analysis of the economic evaluations

Abstract: Background Uncontrolled hyperphosphatemia in chronic kidney disease (CKD) patients commonly results in vascular calcification leading to increased risk of cardiovascular disease. Phosphate binders (PBs) are used for hyperphosphatemia and can be calcium-based (CBPBs) or non-calcium-based (NCBPBs), the latter being more expensive than CBPBs. In this study, we used meta-analysis approaches to assess the cost-utility of PBs for hyperphosphatemia in CKD patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In some cases, the related data were extracted from probabilistic sensitivity analyses, like the cost-effect plane with scatterplot graphs. For studies not reported directly, we calculated the INB and its 95% CI based on the 5 scenarios in line with previous recommendations using the data extracted from the articles (Appendix S2 in the Online Supplementary Document ) [ 22 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In some cases, the related data were extracted from probabilistic sensitivity analyses, like the cost-effect plane with scatterplot graphs. For studies not reported directly, we calculated the INB and its 95% CI based on the 5 scenarios in line with previous recommendations using the data extracted from the articles (Appendix S2 in the Online Supplementary Document ) [ 22 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, meta-analyses on cost-effectiveness studies have only been attempted in 5 studies in different fields of medicine by one other research team [ 21 - 25 ] but not yet in the area of mental health interventions. The theoretical method by Crespo et al [ 20 ] has been practically applied and explained by Bagepally et al [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, Crespo et al [ 20 ] developed a theoretical framework to perform these kinds of analyses. This method has been successfully applied by another research team in several studies in different areas of medicine [ 21 - 25 ]. Currently, no meta-analysis on the cost-effectiveness of internet interventions for mental disorders has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The global burden of chronic kidney disease (CKD) is associated with high economic costs as well as rapidly rising morbidity and mortality. CKD is projected to become one of the leading causes of reduced life expectancy worldwide within the next 20 years [ 1–4 ]. Aggravatingly, chronic kidney disease is expected to exacerbate the financial strain on healthcare.…”
Section: Introductionmentioning
confidence: 99%